Zircon U‐Pb Geochronology Constrains Continental Expression of Great Meteor Hotspot Magmatism. Issue 11 (5th June 2021) - Kinney, S. T.; MacLennan, S. A.; Keller, C. B.; Schoene, B.; Setera, J. B.; VanTongeren, J. A.; Olsen, P. E.
Abstract: The New England‐Québec Igneous Province is considered to be a continental expression of Great Meteor Hotspot magmatism, though other geodynamic scenarios have been suggested. Existing geochronologic data lack the needed accuracy and precision to permit tests of potential causal mechanisms. We provide zircon U‐Pb ages for four igneous centers and a suite of plate reconstructions and show that the duration between magmatism in each branch of this province is ca. 3–6 Myr shorter and ca. 10 Myr older than predicted if the spatial‐temporal distribution of magmatism conformed to a well‐defined age progression. However, in addition to uncertainties in plate reconstructions, variable regional crustal thickness or lithospheric topography likely played a role in mediating the rates of melt transport to emplacement depth and we therefore cannot reject the hotspot hypothesis. Our results place the best‐available chronological constraints on continental magmatism associated with one of the oldest and longest‐lived hotspots. Plain Language Summary: We provide zircon U‐Pb age constraints on a purported episode of continental magmatism associated with the Great Meteor Hotspot. Combined with a suite of plate reconstructions, our results show broad consistency with a hotspot model and provide key chronological constraints on one of the longest‐lived hotspot tracks and the tectono‐magmatic evolution of the Eastern North American Margin. Key Points: Zircon U‐Pb geochronology tests hotspot model for origin of continental magmatism typically associated with the Great Meteor Hotspot New ages indicate a relatively brief episode of magmatism at ca. 122.8–126.1 Ma Modeled hotspot tracks spatially consistent with igneous centers but generally underestimate timing of magmatism by ca. 10 Myr